Pengelolaan Media Sosial untuk Ekowisata: Kawasan Hutan Adat Larang Mude Ayek Tebat Benawa Kota Pagar Alam - Oemar Madri Bafadhal; Adi Inggit Handoko; Annisa Rahmawati; Anang Dwi Santoso (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to provide a comprehension of social media and its ecotourism applications. This event was held in Tebat Benawa Village, Pagar Alam City, from October 8-11, 2022, with 37 ecotourism managers in attendance. The training includes a greater understanding of social media and its use for ecotourism, as well as the creation of a collaborative space for ecotourism promotion between tourists and ecotourism managers. The results of the training demonstrated an increase in comprehension, as evidenced by the pre-test and post-test scores, which ranged from 5.73 to 8.54, and the T-test, which revealed a significant difference between the pre- and post-training periods.